Persepsi Mahasiswa Tentang Cyberbullying di Era Digital - Rusliawan, Sahrul; fathia marlintang ghifarina; bunga srikandi; wisnu hatami (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2024)
The industrial revolution 4.0 with the various information technology products produced is able to change a person’s paradigm and lifestyle in activities. The availability of information via the internet can be easily utilized and disseminated quickly by internet users throughout the world without considering the user’s distance and time limitations. The interaction in it is very active, with various interests and activities carried out so that it is not easy to give control to every internet service user. This behavior forms interactions on the internet between each other to exchange ideas without having to meet, or can be interpreted as sharing information. Existing technological advances have given birth to various forms of social media such as Facebook, Instagram and Twitter. In its development, social media as a medium for sharing information has contributed a lot in changing the behavior of internet users in carrying out social interaction communications. Cyberbullying in the digital era is a form of intimidation, threats and various other forms of bullying carried out through digital technology. Cyberbullying can be carried out via text messages, voice messages, images, or videos, and is usually directed at individuals who are considered weaker or different. The purpose of this research is to find out students’ views on cyberbullying, the role of students in dealing with cyberbullying and students’ attitudes in dealing with people who commit cyberbullying. This research method uses descriptive research methods and also data collection techniques using interviews.